Gender Differences in the Relationships between the Learning Environment and Student Outcomes - Clark, John William (Curtin University, 2022)
This study investigated gender differences in relationships between the learning environment and student outcomes (motivation, self-regulation, mathematics anxiety and achievement) using a sample of 426 university-level mathematics students in the United Arab Emirates. The results suggest that whereas staying on task and completing work was related to student outcomes for all students, social aspects of the learning environment were only related to student outcomes for female students. These findings provide practical information to guide educational improvement.